Imaging of human stem cell-derived dopamine grafts correlates with behavioural recovery and reveals microstructural brain changes - Stephen J. Paisey; Lucy R. Jones; David J. Harrison; Nicola J. Drummond; Olivia Z. Edwards; Maurice A. Canham; Victoria H. Roberton; Christopher Marshall; Greg Parker; Rachel Hills; Anne E. Rosser; Emma L. Lane; et al. (Neurobiology of Disease)
Cell therapy is a promising therapeutic intervention for Parkinson's disease (PD) and is currently undergoing safety and efficacy testing in clinical trials worldwide. The goals of this project were (1) to determine whether [18F]Fluorodopa or [18F]Fallypride imaging correlates robustly with functional recovery; and (2) to explore whether diffusion-weighted MR imaging (DWI) could detect graft-induced cytoarchitectural changes in the host brain. hfVM and hESC-derived dopamine precursor cells were transplanted into the 6-OHDA lesioned rat striatum. Tests of motor function and PET and MR imaging were conducted up to 6 months post-transplantation. Our data demonstrate that [18F]Fluorodopa imaging identified presynaptic DA synthesis from hfVM and hESC-derived dopaminergic grafts and [18F]Fallypride imaging confirmed occupancy and normalisation of D2/D3 receptor expression in the grafted hemisphere. In hfVM grafted rats, [18F]Fluorodopa binding correlated robustly with motor recovery on a range of drug-induced and drug-free behavioural tasks. In hESC-DA grafted rats, improvements in [18F]Fluorodopa PET imaging signals preceded recovery of naturalistic motor behaviours. DWI revealed widespread graft-mediated microstructural changes in the rodent brain, which did not identify graft placement, but instead may reflect remodelling of neuroglia. These data further our understanding of the impact of dopaminergic grafts on brain cytoarchitecture and the potential of these radioligands to predict graft efficacy may aid in the translation of therapeutics from preclinical to clinical settings.